Pertanggungjawaban Pidana Menyampaikan Informasi Palsu yang Membahayakan Keselamatan Penerbangan - Sudaryanto, Rio Sempana Andrean; Sujono, Sujono; Sudarto, Sudarto (Neolectura, 2025)
As a legal state, one of the transportation activities is air transportation. Air transportation is normatively subject to the provisions in Law Number 1 of 2009 concerning Aviation. Based on Article 1 number (1) of the a quo Law, it is known that aviation is a unified system consisting of the use of airspace, aircraft, airports, air transportation, flight navigation, safety and security, the environment, as well as supporting facilities and infrastructure. other general. The research method is normative juridical. The results of the research are: Responsibility for sanctions for perpetrators of criminal acts conveying false information that endangers aviation safety, that liability (criminal) leads to the criminal's conviction, if they have committed a criminal act and fulfill the elements specified in the law. In the researcher's view, there needs to be criminal sanctions in the form of fines or compensation for people on board airplane flights resulting from false information that threatens flight safety. This right can provide a deterrent effect for perpetrators so that they do not harm many people. The judge's legal considerations in Decision Number 43/Pid.B/2018/PN Lbj state that the legal considerations by the Panel of Judges have not provided a deterrent effect, there is a need for sanctions in the form of fines or compensation, so that legal certainty is achieved, because currently there is no legal certainty.